CD73 induces gemcitabine resistance in pancreatic ductal adenocarcinoma: A promising target with non-canonical mechanisms. (28th October 2021) - Yu, Xiaozhou; Liu, Weishuai; Wang, Ziyang; Wang, Hongwei; Liu, Jing; Huang, Chongbiao; Zhao, Tiansuo; Wang, Xiuchao; Gao, Song; Ma, Ying; Wu, Liangliang; Li, Xiaofeng; et al.
Abstract: CD73, a cell surface-localized ecto-5′-nucleotidase, is the major enzymatic source of extracellular adenosine. Canonically, it plays multiple roles in cancer-related processes via its metabolite. As a druggable target, clinical trials targeting CD73 in various malignant diseases are currently ongoing. Here, we report the ecto-5′-nucleotidase-independent functions of CD73 in pancreatic ductal adenocarcinoma (PDAC). Our findings support that the elevated expression of CD73 in PDAC cells promotes gemcitabine (GEM ) resistance by activating AKT. We discovered that a large amount of intracellular CD73 are localized in the endoplasmic reticulum membrane. Intracellular CD73 physically interacts with major vault protein to activate the SRC–AKT circuit. Troglitazone (TGZ) is a peroxisome proliferator-activated receptor gamma agonist that could inhibit the expression of CD73. The administration of TGZ markedly enhances sensitivity to GEM via downregulating CD73 in PDAC. Our findings support that CD73 could be targeted to overcome chemoresistance in PDAC. Highlights: Elevated expression of CD73 in PDAC induces GEM resistance. CD73 functions via a nucleotidase-independent mechanism in PDAC cells. Abundant intracellular CD73 localized in the ER functions via PPIs. Intracellular CD73 physically interacts with MVP to activate the Src–Akt circuit. TGZ enhances sensitivity to GEM via downregulating CD73 in PDAC.